2012
DOI: 10.4103/2006-8808.100346
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-free insertion of distal interlocking screw in tibial and femur nailing: A simple technique

Abstract: Background:Distal interlocking screw insertion in intramedullary nailing of long-bone fracture is a challenging task for orthopedic surgeons. It is difficult particularly when the surgeon is in his learning stage or when image intensifier is not available. We describe a radiation-free technique of distal interlocking screw insertion which is easy and practicable.Materials and Methods:In this technique, a same length nail is placed over the skin (outer nail) and through its distal-most screw hole, a 3.2 mm dril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…[21] In addition, inexpensive and simple methods that reduce radiation exposure and do not require fluoroscopy have also been described. [2,14] Soni RK et al [14] reported that 45 of 47 tibial shaft fractures that they operated with an easy, applicable and no-radiation distal locking screw insertion technique showed complete union and no complications occurred during six months of follow-up. Aldemir et al [2] reported that they operated on 578 tibial fractures without using fluoroscopy with three locking techniques and two control methods, which they described with long years of experience in a very large series, and that failure in the distal locking was seen in only one patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] In addition, inexpensive and simple methods that reduce radiation exposure and do not require fluoroscopy have also been described. [2,14] Soni RK et al [14] reported that 45 of 47 tibial shaft fractures that they operated with an easy, applicable and no-radiation distal locking screw insertion technique showed complete union and no complications occurred during six months of follow-up. Aldemir et al [2] reported that they operated on 578 tibial fractures without using fluoroscopy with three locking techniques and two control methods, which they described with long years of experience in a very large series, and that failure in the distal locking was seen in only one patient.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] On the other hand, inexpensive and simple FHTs, which reduce radiation exposure in distal screwing, have been described. [2,14] In this study, we aimed to compare the results of FHT and EMGS results of the distal locking method concerning surgery duration and radiation exposure in patients who underwent osteosynthesis of tibia fractures with IMN.…”
Section: Intramedullary Nailing (Imn) Technique Is the Gold Standard mentioning
confidence: 99%
“…Smallest available cannulated nail of 8 millimeters size was passed over guide-wire. Distal locking was done free hand using technique described by Soni and Mehta et al [2]. Proximally two bolts were inserted with jig [ Fig.3].…”
Section: Case Reportmentioning
confidence: 99%
“… 6 Rohilla et al and Soni et al described the nail-over-nail technique to simplify distal locking and decrease radiation exposure. 7 , 12 Nail mounted jig techniques have been developed by multiple companies, including Orthofix (Verona, Italy), Stryker (Kalamazoo, Michigan), Synthes (Zuchwil, Switzerland) and the surgical implant generation network (SIGN) nail. 13 18 The inherent problem with these nail-mounted techniques is the slight deformation that femoral nails undergo during insertion into the intramedullary canal.…”
Section: Introductionmentioning
confidence: 99%